2016
DOI: 10.1002/cam4.685
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with nonmetastatic muscle‐invasive bladder cancer not undergoing cystectomy after treatment with noncisplatin‐based chemotherapy and/or radiotherapy: a retrospective analysis

Abstract: Transurethral resection of bladder tumor (TURBT), radiotherapy, chemotherapy, or combinations can be used in patients with muscle‐invasive bladder cancer (MIBC) not undergoing cystectomy. Nevertheless, unfitness for cystectomy is frequently associated with unfitness for other therapeutic modalities. We report the outcome of patients with MIBC who did not undergo cystectomy and did not receive cisplatin‐based chemotherapy. Selection criteria for the study were nonmetastatic MIBC, no cystectomy, no cisplatin‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Two studies reported measures of comorbidity. The study by Bamias et al, [ 26 ] which was excluded from our meta-analysis, reported a median Charlson comorbidity score of 5, which is associated with a significantly elevated mortality rate in the perioperative setting, for their entire study group [ 30 ]. Among this group, patients receiving systemic chemotherapy + TURBT were only those deemed unfit for radical cystectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported measures of comorbidity. The study by Bamias et al, [ 26 ] which was excluded from our meta-analysis, reported a median Charlson comorbidity score of 5, which is associated with a significantly elevated mortality rate in the perioperative setting, for their entire study group [ 30 ]. Among this group, patients receiving systemic chemotherapy + TURBT were only those deemed unfit for radical cystectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to compare systemic chemotherapy regimens (carboplatin-based vs. cisplatin-based) were limited by a lack of power deriving from unbalanced subgroups. Of the four studies that used carboplatin-based regimens, one [ 26 ] included only patients who were deemed “unfit for radical cystectomy” and reported 20% overall survival at 5 years, [ 26 ] while the others either included patients who refused RC [ 9, 34 ] or did not specify the reason for bladder sparing, [ 23 ] and reported rates closer to the 72% 5-year survival estimated by this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual crude incidence rate is 20.4/100000, while in 2012, the annual crude mortality rate was 7.1/100,000. Most cases present with non-invasive disease, but about one third of these patients will progress to muscle-invasive disease, while 30% exhibit muscle invasion with or without metastases upon diagnosis ( Howlader et al, 2016 ; Bamias et al, 2016 ). Radical cystectomy (RC) with pelvic lymph node dissection (LND) is the treatment of choice ( Bellmunt et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%